ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS DALAM MENYELESAIKAN SOAL BANGUN DATAR PADA SISWA KELAS VIII.B MTS MUHAMMADIYAH LIKUBODDONG KABUPATEN GOWA - sitti rahmah tahir; St.Nur Humairah Halim; Muhammad Zhaahir Nurjam (Mandalika Mathematics and Educations Journal, 2022)
This study aims to analyze the mathematical critical thinking skills of eighth grade students of MTs Muhammadiyah Likuboddong in the 2020/2021 academic year in solving flat shape problems. This research is a research that uses a descriptive qualitative approach which is designed to determine the students' mathematical critical thinking skills in solving problems of flat shapes. The data analyzed is the data of students' mathematical critical thinking skills. The data collection method used is the provision of essay tests and interviews. The questions used in measuring students' mathematical critical thinking skills, totaling 3 questions, are questions that contain indicators of students' mathematical critical thinking abilities. These questions were done by 15 students in 35 minutes and the interviews aimed to determine the students' ability to think critically mathematically. Based on the results of the study, it can be concluded that the students' mathematical critical thinking skills in class VIII.B Mts fulfills the indicators of mathematical critical thinking